Planejamento estratégico participativo na cooperativa de Agricultores Familiares de São Miguel do Guamá (PA) - FIGUERÊDO, Pâmela Rafyza Rabelo (2022)
Management tools, previously used only in private organizations, have been increasingly applied in different types of enterprises, adapted and re-signified to each reality. The implementation of tools in the environment, allow the use of management tools that are able to reduce the levels of uncertainty and which paths can be followed to achieve the desired future. Reflecting on the subject, the present work has as objective the elaboration of a Participatory Strategic Planning that meets the reais of the Cooperativa dos Agricultores Familiares Guamaenses - COAFAG which is located in the northeast of Pará. Participatory Strategic Planning allows for participation, integration and approximation with workers, in addition to encouraging dialogue, commitment and satisfaction of belonging to a given reality. For its construction, instruments such as the participatory diagnosis were used, making use of the SWOT management tool in support of the construction of organizational identity, using participatory methodologies in order to analyze management, political, socioeconomic aspects and identification by the cooperative members themselves the critical points to be addressed. be improved and the favorable points to be explored in the management orientation of the enterprise in the context of Solidarity Economy. In order to gather the necessary information and build the Participatory Strategic Planning, the research was based on action research references, face-to-face meetings were held at the cooperative's headquarters, during the first and second semesters of 2021, in a collective and democratic way. The process was entirely planned, built and executed together with the cooperating family farmers. The collective of associated workers participated debating about the trajectory and perspectives of the cooperative and based on that, the Planning with the Action Plan was created. It was observed that, if, on the one hand, the financial issue, low personal motivation and dependence on middlemen are the main weaknesses and threats to the cooperative, generally common to cooperatives in the beginning of their organization; on the other hand, the high willingness of the collective to dialogue about the need for changes in the management of work and production is fundamental, especially with the close presence of educational institutions committed to supporting the growth and development of the solidarity enterprise and the expansion of activities in support of family farming cooperativism. It is concluded that the Action Plan can contribute to the organization and development of the cooperative, as long as there is a real engagement of all and the commitment to follow the priorities set by them.